Measurement of CP observables in B ± → DK ± and B ± → Dπ ± with D → K S 0 K ± π ∓ decays - Aaij, R; Abellán Beteta, C; Ackernley, T; Adeva, B; Adinolfi, M; Afsharnia, H; Aidala, CA; Aiola, S; Ajaltouni, Z; Akar, S; Albicocco, P; Albrecht, J; et al. (Springer, 2020)
Measurements of CP observables in B± → DK± and B± → Dπ± decays are presented, where D represents a superposition of D0 and D¯0 states. The D meson is reconstructed in the three-body final states KS0K±π∓ and KS0K∓π±. The analysis uses samples of B mesons produced in proton-proton collisions, corresponding to an integrated luminosity of 1.0, 2.0, and 6.0 fb−1 collected with the LHCb detector at centre-of-mass energies of s = 7, 8, and 13 TeV, respectively. These measurements are the most precise to date, and provide important input for the determination of the CKM angle γ.